Physics in Sport Education: Insights from a decade of bibliometric analysis (Program Studi Ilmu Keolahragaan - Universitas Pendidikan Indonesia, 2024)
This study aims to analyze the trends in scientific publications related to the application of physics in sports education over the past decade using a bibliometric approach. Data was collected from the Scopus database using the keywords